Synthesis and use of SBA-15 adsorbent for dye-loaded wastewater treatment. Issue 4 (December 2015) - Chaudhuri, Haribandhu; Dash, Subhajit; Sarkar, Ashis
Graphical abstract: Highlights: SBA-15 was found to have very high adsorption capacities towards NR and SF dyes. Such adsorption capacities of SBA-15 may be correlated to its structural features. The regeneration capacities of the material are also high. Abstract: Adsorption of four dyes, namely neutral red (NR), safranin O (SF), reactive red 2 (RR2) and congo red (CR), onto SBA-15 (Santa Barbara Amorphous) material was studied in detail not only to investigate the possible effects of interactions between adsorbate molecules and adsorbent but also the potential of this material for the removal of dyes from wastewater. SBA-15 and dye adsorbed SBA-15 were thoroughly characterised using standard analytical tools. High resolution X-ray diffractogram (HR-XRD) of SBA-15 shows four distinct peaks characteristic of highly ordered mesoporous material. Peak intensities of diffractograms of dye adsorbed SBA-15 are less intense. Nitrogen adsorption-desorption isotherm of SBA-15 is type-IV typical of mesoporous material. Such isotherms of dye adsorbed SBA-15 are different from that of SBA-15. Specific surface area, average pore diameter, and total pore volume decreased on adsorption of dyes- clearly indicating that pores have been blocked. High resolution transmission electron microscopic (HR-TEM) analyses of SBA-15 and dye adsorbed SBA-15 show distinct changes in pore morphology. It is observed that the adsorption capacities of SBA-15 towards NR and SF are much greater in comparison to RR2 and CR. The adsorption kinetics and isotherm follow the pseudo-second-order kinetics model, intraparticle diffusion kinetics model and Langmuir adsorption isotherm model respectively. The thermodynamic parameter suggests that the dye uptake process is spontaneous. The high adsorption capacity of SBA-15 ( q m = 289.86 mg g −1 for NR, q m = 257.73 mg g −1 for SF) is probably due to electrostatic interactions as well as H-bonding interactions between adsorbent and adsorbate molecules.